Uncovering the Role of the Epithelial-Mesenchymal Transition in Ovarian Cancer Immunogenicity - Yakubovich, Edward (Université d'Ottawa | University of Ottawa, 2024)
Cancer cells often metastasize by undergoing an epithelial-mesenchymal transition (EMT). While undergoing EMT, epithelial cells lose defining characteristics, such as stable cell-cell junctions, and gain the ability to migrate and invade through extracellular matrices. In addition to these changes in characteristics, mesenchymal cells gain the ability to better regulate the immune system around them. Immune regulation by mesenchymal cells in cancer has been a topic of extensive study and has recently started receiving focus in ovarian cancer. Combined with the emergence of advanced single-cell sequencing techniques, there is now great potential in unraveling the interactions underlying immune regulation by mesenchymal cells and the contribution of the EMT to the phenomenon of immunosuppression in cancer. Here, I present my studies applying a combined approach of single-cell transcriptomics (scRNA-seq) and lab-based techniques to characterize the relationship between the EMT and immune regulation in ovarian cancer. First, by characterizing human ovarian tumors and murine ovarian cancer models I identified that mesenchymal cells secrete chemokines and interleukins into their environment such as CCL2, CCL5, and IL1A. The primary immunosuppressive factor secreted by mesenchymal cells against NK cells was determined to be TGF-β1. I also discovered a possible link between infiltration of immune cells into the tumor microenvironment (TME) and EMT where greater numbers of mesenchymal cells in the TME correlated with a greater number and variety of immune cells in both human ovarian tumors and murine ovarian cancer models. Second, by cell-cell communication analysis of scRNA-seq data, I discovered that LGALS3 expressed by mesenchymal cells may exhaust CD8⁺ T-cells through the LAG3 receptor in human ovarian cancers. Finally, I uncovered links between EMT and the antigen presentation machinery of ovarian cancer cells where higher expression levels of major histocompatibility complex I (MHC I) positively correlated with the presence of mesenchymal cells in the TME. This work further expands the knowledge base of EMT and immunosuppression in ovarian cancer and can be used to inform researchers and clinicians on new targets and mechanisms for future research and therapy, such as targeting the LGALS3-LAG3 axis in ovarian cancer to relieve exhaustion of T-cells.
Keywords: ovarian cancer; bioinformatics; epithelial-mesenchymal transition; cancer; EMT